2017
DOI: 10.3389/fimmu.2017.01437
|View full text |Cite
|
Sign up to set email alerts
|

The Equivocal Role of Th17 Cells and Neutrophils on Immunopathogenesis of Leishmaniasis

Abstract: Advances in the understanding of leishmaniasis progression indicate that cellular interactions more complex than the Th1/Th2 paradigm define the course of infection. Th17 cells are a crucial modulator of adaptive immunity against Leishmania parasites acting mainly on neutrophil recruitment and playing a dual role at the site of infection. This review describes the roles of both these cell types in linking innate defense responses to the establishment of specific immunity. We focus on the Th17–neutrophil intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
103
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 101 publications
0
103
0
3
Order By: Relevance
“…IL-17 is a potent activator of neutrophils, both through lineage expansion and through their recruitment by regulating chemokine expression. While IL-17 perturbation was not identified in our whole blood transcriptional profiles associated with human VL, evidence from murine models [51] demonstrate a strong role for IL-17 and neutrophils in parasite clearance from liver and spleen. Duthie and coworkers [50] have shown that both IL-10 and IL-17 cytokines are elevated in the serum of active VL patients, reverting to baseline levels with standard antimonial treatments.…”
Section: Discussionmentioning
confidence: 83%
“…IL-17 is a potent activator of neutrophils, both through lineage expansion and through their recruitment by regulating chemokine expression. While IL-17 perturbation was not identified in our whole blood transcriptional profiles associated with human VL, evidence from murine models [51] demonstrate a strong role for IL-17 and neutrophils in parasite clearance from liver and spleen. Duthie and coworkers [50] have shown that both IL-10 and IL-17 cytokines are elevated in the serum of active VL patients, reverting to baseline levels with standard antimonial treatments.…”
Section: Discussionmentioning
confidence: 83%
“…Once inoculated into the host dermis by an infected sandfly, infective metacyclic promastigotes of Leishmania are engulfed by a variety of immune cells, such as resident dermal dendritic cells, macrophages and infiltrating neutrophils that act as the first line of defense [20][21][22][23][24]. The rapid and massive recruitment of neutrophils to the site of parasite inoculation has been well documented and associated with the enhancement of the disease [20][21][22]. Neutrophil-driven inflammation seems to be mostly triggered by the insertion of the sandfly's proboscis into the skin, provoking tissue damage [24,25].…”
Section: Early Eventsmentioning
confidence: 99%
“…Meantime, an anti-inflammatory phenotype is correlated with a predominant Th2 response characterized by the production of IL-4, IL-13, IL-10, and Transforming Growth Factor (TGF)-β cytokines; enhanced arginase activity; polyamine biosynthesis; and IL-21-mediated down-regulation of iNOS, TNF-α, and Toll-like receptor (TLR)-4, favoring intracellular proliferation of Leishmania parasites and disease progression [56,57] (Figure 2). Additionally, the role of other T cell subtypes in Leishmania pathogenesis, such as T regulatory cells (Treg), CD8+ T cytotoxic, and Th17 effector cells, is coming to light [20,58,59]. Th17 cells are suggested to participate in the balance of inflammatory cytokines, modulating adaptive immunity, and also secret the IL-17 cytokine that contributes to neutrophil recruitment [20].…”
Section: The Adaptive Immune Responses In Leishmaniasismentioning
confidence: 99%
See 2 more Smart Citations